Perilaku Merokok Berubungan dengan Aliran Puncak Ekspirasi Pria Dewasa - Srimiyati, Srimiyati; Ajul, Keristina; Surani, Vincencius (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the relationship between smoking behavior and peak expiratory flow in adult men. The method used is a descriptive correlation with a cross-sectional approach. The total research sample was 67 respondents taken using the purposive sampling technique. The instrument used was a questionnaire to measure age and smoking behavior, while peak expiratory flow was measured using a peak flow meter. Data analysis used the Kendall tau_b test. The research results show that the p-value is 0.003 and τ = -.347. In conclusion, there is a significant relationship between smoking behavior and peak expiratory flow in adult men with a weak correlation level and tends to have a negative direction. Keywords: Peak Expiratory Flow, Smoking Behavior, Breathing, Adult Men, Cigarettes